2022
DOI: 10.1002/agj2.21009
|View full text |Cite
|
Sign up to set email alerts
|

The optimal reference gene validation in Cyclocarya paliurus (Batal.) Iljinskaja under environmental stresses

Abstract: Cyclocarya paliurus (Batal.) Iljinskaja is a special plant species grown at high elevation in southwestern China. The bark, leaves, and roots are used for many purposes including reduction of fever and enhancement of blood insulin level. However, its growth is usually limited by the fragile environment and climate variability. Previous studies attributed the environment‐relevant yield reductions to stress induced gene expression changes. The accuracy and reliability of reverse transcription quantitative polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…(2022) and in Cyclocarya paliurus Iljinskaja, a special plant species grown at high elevation in southwestern China, by Yang, Fan, et al. (2022). The authors noted that GAPDH gene was identified as the best reference gene.…”
Section: Resultsmentioning
confidence: 99%
“…(2022) and in Cyclocarya paliurus Iljinskaja, a special plant species grown at high elevation in southwestern China, by Yang, Fan, et al. (2022). The authors noted that GAPDH gene was identified as the best reference gene.…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA synthesis was carried out using Moloney murine leukemia virus (M-MLV) reverse transcriptase from Invitrogen, following the instructions provided by the manufacturer. To ensure precise quantification, the 18S RNA was utilized as a normalization control for the quantity of cDNA [40]. RT-PCR analysis was performed to investigate the splicing of CpbZIP11.…”
Section: Mrna Splicing Assay and Rt-pcrmentioning
confidence: 99%
“…Furthermore, there is evidence for strong health-promoting effects of its leaves, including the ability to lower blood sugar, reduce blood lipids, protect against cancer, and enhance immunity [ 24 ]. The growth and development of C. paliurus leaves are affected by environmental stress, such as drought, salt, cold, and heat [ 25 ], and various TFs contribute to the regulation of growth in C. paliurus leaves. For example, bZIP is involved in the regulation of amino acid biosynthesis [ 26 ], and MYB and bHLH are involved in the regulation of flavonoid biosynthesis [ 27 ].…”
Section: Backgroudmentioning
confidence: 99%